Bird's eye view of Port of Spain, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
Photo showing an aerial view of Port of Spain, Trinidad. Buildings, vegetation and a roadway are visible in the photo.
Colour: Sepia; Style: Landscape ; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Roofs--Trinidad and Tobago; Streets--Trinidad and Tobago